Zeitgenössische Kunst in der Deutschen Bank Frankfurt. (Frankfurt am Main : Deutsche Bank AG, 1987)
Adamski, Hans Peter ; Albers, Josef ; Altenbourg, Gerhard ; Antes, Horst ; Anzinger, Siegfried ; Auberger, Pidder ; Bach, Elvira ; Baschang, Hans ; Baselitz, Georg ; Bayrle, Thomas ; Becher, Bernd und Hilla ; Beuys, Joseph ; Bill, Max ; Blume, Bernhard Johannes ; Bömmels, Peter ; Bohrmann, Karl ; Bordanowicz, Jürgen ; Brodwolf, Jürgen ; Broodthaers, Marcel ; Brosch, Hans ; etc.
boek